Globalisasi:Intervensi kekuatan politik dan ekonomi dalam pembentukan hukum dan pengusahaan migas di Indonesia - -, Sugiaryo - (refleksi hukum)
Abstract The relation of international economical and politic in globalization era is indeed very closely. Both of them have casual inter influencing and dynamic in their natures. Big and strong countries are much more provide their influences, seven frequently insisting on their intention using varied premises. The frequently proposed premised are in relation with human being rights. Conversely, small countries, developing countries and politically and economically weak countries are much more depending on global level. The oil and gas law establishment in Indonesia, United Stated through USAID, in cooperation with Indonesian governmental officers with the involvement of NGO, universities and media provide funds to arrange draft of Oil and gas acts year of 2000. The draft Â of oil and gas Acts there after had stipulated to be the Acts No. 22/2001. In this Acts, there are orders from United States especially in Article 28 verse 2 in which confirming that prices of fuel and oil and also earth gas is delegated to health and fair business competition mechanism. For such importance, for it can be successful, then there also emerging a policy that each debt from IMF, World Bank and ADB had conditioned that the debtor must implement privatization, deregulation and fuel and oil subsidy cancellation to follow the market price. Although the acts No. 22/2001 had been stipulated, but in the implementation, specifically for article 28 verse 2 and 3, they have been experience obstruction due to Pertamina Unions had proposed accuasation to the court of Constitution on the violation of such acts with the article 33 of 1945 Constitution. And in the trial result by the Court of Constitution, the article 28 verse 2 and 3 had cancelled and having no legal authorization. The cancellation of the article by the Court of Constitution, in fact, is not giving obstruction for the United States wish to hold intervention because they keep try in substituting a new term, that is the term market price which by the Court of Constitution had been banned is replaced with the term economical price. It is shown from the governmental policy in 2005, 2007 and 2009 which stated the price increment on oil and fuel, especially subsidized premium. And if in last 1 December 2008 the price decreased. And decreased in 15 December 2008, they were due to the decrement of world oil price. Keywords : Globalization, intervention, political and economical power, law establishment and oil and gas business.